Safety and Efficacy of Flow Diversion for Intracranial Aneurysms in Small Parent Vessels: A Retrospective Cohort Study - Abdelaziz, Mohamed Ali; Egila, Hossam; El-Mitwally, Ashraf; Spelle, Laurent; Sobh, Khaled; Elmenshawi, Ibrahim (International Journal of Statistics in Medical Research, 2025)
Background: Intracranial aneurysms arising from small parent vessels (<2 mm) are challenging due to their fragile anatomy and distal locations. Flow diversion (FD) offers a promising treatment, but its safety and efficacy in small vessels remain underexplored. Objective: To evaluate angiographic occlusion rates and procedure-related morbidity associated with flow diversion for intracranial aneurysms arising from parent vessels <2 mm in diameter. Methods: A retrospective cohort study was conducted at Bicêtre Hospital, Paris, France, from January 2018 to December 2023, analyzing 50 patients undergoing 56 procedures for 55 aneurysms. FD devices (e.g., Silk Vista Baby, Pipeline Flex) were used. Follow-up at 6, 18, and 42 months assessed occlusion via digital subtraction angiography (DSA) using Raymond-Roy and O’Kelly-Marotta scales. Results: Complete occlusion was achieved in 70.9% (39/55) of aneurysms at a mean follow-up of 17.86 months. At 6, 18, and 42 months, occlusion rates were 56.4%, 55.6%, and 76.5%, respectively. Intraprocedural complications occurred in 28.6% (16/56) of procedures, with 19.6% (11/56) due to in-stent thrombosis. Symptomatic major complications were observed in 17.9% (10/56), including ischemic events and hemorrhage, and permanent FD-related morbidity was 8.0% (4/50). Conclusion: FD is effective for small vessel aneurysms, with high occlusion rates, but significant complications highlight the need for careful patient selection and refined techniques. Larger studies are needed to optimize outcomes.